2006
DOI: 10.4102/ids.v40i1.333
|View full text |Cite
|
Sign up to set email alerts
|

Die aanwending van Rolf Zerfass se handelingswetenskaplike model in prakties-teologiese teorievorming – ’n gereformeerde perspektief

Abstract: Utilising Rolf Zerfass’s operational scientific model in developing practical-theological theory – a reformed perspective Rolf Zerfass’s operational scientific model for correcting Christian-ecclesiological praxis is frequently utilised in practical- theological research at the North-West University. At face value Zerfass’s model seems to serve as an ideal framework in guiding a practical-theological study through all the relevant methodological phases – emphasising the cycle needed to move from a probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…De Wet (2006, p. 68) observed that practical theological thinking informed Zerfass's approach in the 1960s where 'questions were asked about the relevance of the Christian faith for the present' (De Wet 2006, p. 69). De Wet's (2006) most insightful critique of Zerfass's model is his comment on the context of its development, which is Bastian's theology questions. However, De Wet's evaluation is limited to the model's Reformed theological application utility.…”
Section: About North-west University Practical Theologymentioning
confidence: 99%
“…De Wet (2006, p. 68) observed that practical theological thinking informed Zerfass's approach in the 1960s where 'questions were asked about the relevance of the Christian faith for the present' (De Wet 2006, p. 69). De Wet's (2006) most insightful critique of Zerfass's model is his comment on the context of its development, which is Bastian's theology questions. However, De Wet's evaluation is limited to the model's Reformed theological application utility.…”
Section: About North-west University Practical Theologymentioning
confidence: 99%